MOLECULAR IDENTIFICATION OF BABYLONIA SPIRATA (MOLLUSCA: GASTROPODA: BABYLONIIDAE) BASED ON 18S RRNA GENE - G. Chelladurai (Journal of Indian Fisheries Association, 2017)
The spiral babylone, Babylonia spirata is the most important of economical marine gastropod for human consumption and ornamental purposes. The present study deals with the molecular taxonomy of Babylonia spirata. Amplification products of B. spirata obtained with the primers 18SIF (forward) and 18S2R. Kimura-2-Parameter genetic distance, nucleotide composition and neighbour joining analyses shows that Babyloniidae is clustered closely with Hemifusus sp of super family of Buccinoidea. Additional gene data and increased sampling are warranted to give new insights into the phylogenetic relationship between all Indian species of Neogastropoda.